Does renewable energy increase farmers' well-being? Evidence from solar irrigation interventions in Bangladesh - Monzur Hossain; Azreen Karim (Asian Development Bank Institute (ADBI), 2020)
As an alternative clean and climate-friendly energy source, renewable energy has gained increased importance in government policies, in particular regarding the use of sun power to operate irrigation projects. Researchers have found solar-power-based irrigation projects to be reliable, sustainable, and cost-effective, with higher rates of return, and recent studies have mostly focused on these outcomes. In the effort to ensure maximum electricity coverage in off-grid regions by 2041 and to achieve the global agenda of SDG 7, the Government of Bangladesh has recently prepared a draft policy to purchase unconsumed or surplus electricity from solar-run irrigation pumps (SIPs) across the country with the aim of promoting renewable energy, which further laid down the motivation for understanding the impacts of such interventions from the point of view of beneficiaries' well-being. Therefore, this paper particularly looks at the beneficial impacts of solar-powered irrigation using a recent survey of 1,000 solar-powered irrigation user and non-user farming households in selected regions of Bangladesh. Our regression results suggest that solar irrigation facilitates an adequate water supply and reduces the cost of production. However, the IV regression results suggest that SIPs do not significantly increase the agricultural return across all the seasons or plots. Overall, SIP adoption ensures reliability of the water supply (i.e., water adequacy) in addition to accessibility and affordability, implying longer-term implications for farmers' well-being.
Keywords: Q15; Q16; Q42; 330; renewable energy; solar irrigation; agricultural productivity; farmers' well-being; Bangladesh